Efficiency Analysis Of Airports In Turkey Considering Environmental Effects - Berna H. Ulutas (The Central European Review of Economics and Management (CEREM), 2018)
Aim: This paper aims to attract attention to the "green airport" term that is basically related with environmental legislations.Design / Research methods: A Data Envelopment Analysis (DEA) model is introduced to assess the efficiency of 22 airports in Turkey with the definition of undesirable output as emission values.Conclusions / findings: Results illustrate that only two airports are efficient based on the considered outputs and undesirable output.Originality / value of the article: Up-to-best knowledge, green gas emission data of airports in Turkey are considered in a DEA model for the first time. To minimize the undesirable output, it is considered as a desirable input in the model. Results are expected to support official authorities during decision making.Limitations of the study: Data for noise levels and the exposed area and/or number of exposed people and buildings were not available for the airports in concern.
Keywords: L93; L98; O18; O44; Q53; R11; R15; 330; airport efficiency; data envelopment analysis; undesired outputs; environmental factors; noise level; handicap friendly airport; green airport